(untitled) (Global Journal of Science Frontier Research, 2022)
Heavy metal soil pollution had increased in recent years and this has produced adverse effects to human wellbeing s health by being uptaken in the food chain A potential threat of heavy metal pollution was suspected at the Government Farm in G ammieri This is due to heavy traffic and fireworks causing concern to the farmers who cultivate fruit and vegetables in these fields Soil sampling with an instrument that can give rapid results was needed to analyse the data and give the real-time in-situ mapping of heavy metal pollution in the soil